2011
DOI: 10.1037/a0022887
|View full text |Cite
|
Sign up to set email alerts
|

Spousal support and changes in distress over time in couples coping with cancer: The role of personal control.

Abstract: This longitudinal study has examined the associations between perceived supportive and unsupportive spousal behavior and changes in distress in couples coping with cancer. We tested whether people relatively low in their sense of personal control were more responsive to spousal supportive and unsupportive behavior than were people relatively high in personal control. Patients with colorectal cancer and their partners (n = 70) completed questionnaires at two assessment points: 3 (at baseline) and 9 months (at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 48 publications
4
30
0
Order By: Relevance
“…Benyamini et al, 2007;Sterba & DeVellis, 2009), as well as that dyadic behaviour is important for both partners' adaptation to illness and well-being (e.g. Badr et al, 2010;Dagan et al, 2011;Mellon et al, 2007). It seems that, within a dyadic context, partners probably take due account of each other's illness-related beliefs and experience,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benyamini et al, 2007;Sterba & DeVellis, 2009), as well as that dyadic behaviour is important for both partners' adaptation to illness and well-being (e.g. Badr et al, 2010;Dagan et al, 2011;Mellon et al, 2007). It seems that, within a dyadic context, partners probably take due account of each other's illness-related beliefs and experience,…”
Section: Discussionmentioning
confidence: 99%
“…Mellon, Kershaw, Northouse, and Freeman-Gibb (2007) reported that the dyadic family stress and the dyadic meaning of illness were related to the fear of recurrence in a sample of cancer survivors and their partners. Dagan et al (2011) showed that spousal support was important for both cancer patients and their partners, but only when they reported relatively low levels of personal control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who use maladaptive coping strategies such as avoidance (disengaging from a stressor instead of directly addressing it), blaming self (focusing on self-blaming instead of actively trying to address the stressor), and who experience feelings of helplessness in the face of dealing with HIV may benefit more from social support, because they are at higher risk for poorer outcomes compared to individuals who do not use maladaptive coping strategies or who do not experience feelings of helplessness, and thus stand to gain more from social support. Indeed, studies suggest that individuals low in personal control (Dagan et al, 2011) benefit more from social support compared to individuals high in personal control. This may be due to those with high levels of personal control having ceiling functioning on outcomes, with not much room for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The person receives support from their family or significant people in their life when they feel their abilities are inadequate or worn out. It has been reported that social support affects physical and emotional health positively by meeting fundamental social needs such as love, compassion, and belonging to a group, and is a significant help for the person in coping with difficulties in life (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%